Spatial Spillover Effect of East Java Economic Growth - Andiga Kusuma Nur Ichsan; Yessi Rahmawati; Fitria Nur Anggraeni (Kantor Perwakilan Bank Indonesia Provinsi Jawa Timur, 2022)
The present study tries to examine the strategic role of East Java’s economic performance toward national level in spatial-based development. In spatial views, the economics of East Java statistically significant to improve economic growth in the neighboring area or provinces, and also support the East Java’s economic growth itself. The methodology uses for the present study consists of two methods, that are Inter-Regional Input-Output (IRIO) and Spatial Econometrics. First, the IRIO analysis shows the existing of Inter-Regional Spillover Effect in economics of East Java Province. Next, the authors examine if the economy of East Java Province experiences positive growth, it will encourage output growth in Java Island and improve the value added in eastern of Indonesia. Second, the result of SDM confirm that the existing of spatial spillover effect in Inter-Regional Economic of East Java Province. The result confirms the key role to boost economic growth of district/cities in East Java Province, is not only influenced by the region itself (local economy) but also support by spatial interactions with other regions (neighborhood or neighbors). The present study also finds that the neighboring GDRP per capita with other determinants i.e., capital, share of the agriculture sector, share of manufacturing industry and share of the service sector and local government spending have a significant effect on enhancing economic growth in East Java Province. The authors note that it is necessary to consider a spatial framework and approach. One of the policy recommendations in order to encourage economic growth in East Java is to strengthen the Local Value Chain (LVC) in strategic sectors, especially by encouraging inter-regional cooperation.